Comparing the Effects of Intracellular and Extracellular Magnetic Hyperthermia on the Viability of BxPC-3 Cells - Prina Mello, Adriele (My University, 2020)
Magnetic hyperthermia involves the use of iron oxide nanoparticles to generate heat in tumours following stimulation with alternating magnetic fields. In recent times, this treatment has undergone numerous clinical trials in various solid malignancies and subsequently achieved clinical approval to treat glioblastoma and prostate cancer in 2011 and 2018, respectively. However, despite recent clinical advances, many questions remain with regard to the underlying mechanisms involved in this therapy. One such query is whether intracellular or extracellular nanoparticles are necessary for treatment efficacy. Herein, we compare the effects of intracellular and extracellular magnetic hyperthermia in BxPC-3 cells to determine the differences in efficacy between both. Extracellular magnetic hyperthermia at temperatures between 40-42.5 °C could induce significant levels of necrosis in these cells, whereas intracellular magnetic hyperthermia resulted in no change in viability. This led to a discussion on the overall relevance of intracellular nanoparticles to the efficacy of magnetic hyperthermia therapy.
PUBLISHED
Keywords: Cancer; Iron oxide nanoparticles; Magnetic hyperthermia; Magnetic nanoparticles